Comparison of Ethanol Levels in Yellow and Red Watermelon Wine - Tan, Andreas Felix; Manao, Mutiara Angelina; Delviyanti, Maria Novia; Honesty, Pricillia Pretty Septy; Hapsari, Natalia Diyah (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Watermelon is one of the tropical fruits that has high water and sugar content. However, the selling price of watermelon is still relatively low, and there is limited processing variation. By utilizing the high water and sugar content in watermelon to create an alcoholic beverage, wine is one promising form of innovation. The aim of this research is to determine the difference in alcohol content of wine made from yellow and red watermelon. The samples used in this study were yellow and red watermelons. Yellow and red watermelons fermented with Saccharomyces cerevisiae yeast to transform them into wine. The ethanol content in wine and red watermelons was analyzed using GC-MS instruments. Subsequently, the soluble sugar content, pH, IR spectra, as well as the color, taste, and aroma of the wine also analyzed. The research results show that the average ethanol content of yellow and red watermelon wines is 7.59% and 6.61% respectively. The average soluble sugar content in yellow and red watermelon wines is 8.6% Brix and 12.64% Brix, respectively. The pH value of each wine sample is 4, and the IR spectra of each wine sample indicate the presence of stretching OH groups. In conclusion, red watermelon wine has a lower ethanol content than yellow watermelon wine.